Rancang Bangun Aplikasi Belajar Membaca Al-Qur'an Berbasis Android - Fadhil Naufal Shodiq; Rachmat Adi Purnama; Sujiliani Heristian (LPPM Universitas Bina Sarana Informatika, 2021)
Reading the Al-Qur'an has always been a culture of Indonesian society, however recently the Al-Qur'an has begun to be abandoned. Muslims are more engrossed in following games and social media with fun playing than opening the Al-Quran mushaf. In order not to have hijaiyah illiterate young people, they must carry out learning that follows the present era, such as learning applications that are not inferior to applications that make young Muslims lazy, the main target in the learning method of reading the Al-Quran application is children at an early age to learn it because children at an early age have quite good comprehension and memory. Based on the background that the authors convey above, the authors are interested in conducting further research on learning methods based on reading the Al-Quran application. The system development method used in this study uses the RAD (Rapid Application Development) Model. Rapid Application Development (RAD) is a software development process model that is incremental, especially for short processing times. The results of the research show that learning with an interactive system increases children's interest in starting the initial learning process. In addition, interactive games are an alternative in conveying learning among other methods.